Obraz Niemca na Ziemiach Zachodnich na łamach "Głosu Wielkopolskiego" w latach 1945-1948 = The image of Germans in the Western Territories in "Głos Wielkopolski" ("Voice of the Wielkopolska Region") in 1945-1948 - Bartkowiak, Przemysław (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
In the years 1945-1948, "Głos Wielkopolski" raised widely the issue of the remaining German population in the area of the Western Territories. A selection of the articles discussed here, which were responsible for creating the image of the Germans in the Western Territories, was made on the basis of studies of the above-mentioned daily newspaper. It is certainly only a part of the rich materials presented on its pages and has a very subjective character. However, it constitutes an interesting overview of the conditions which directly helped to shape the new society of the Western Territories. It should be noted that, in general, "Głos Wielkopolski" picked up accurately on, and reliably presented, the attitudes of Polish settlers in relation to the German population, including their expectations and concerns, condemning disturbing attitudes, behaviour and phenomena such as the economic exploitation of German workers. To sum up, it can be noted that "Głos Wielkopolski" was a reliable source depicting the image of contemporary Polish-German relations in the Western Territories in 1945-1948.
Keywords: Ziemie Zachodnie; Niemcy; badania naukowe; prasa codzienna; prasoznawstwo; Głos Wielkopolski (czasopismo); Western Lands; Germany; scientific research; daily press; press studies